Instructional Principal Leadership in Merdeka Curriculum Implementation (DPL-8): CIPP Evaluation in Senior High Schools - Tri Wahyu Widodo; Alan Lutfi Gesang Saputra; Sumarno Sumarno; Ahmad Farhan Rifan Najib (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines how principal leadership supports the implementation of the Merdeka Curriculum at Sambungmacan 1 Public Senior High School using the CIPP (Context, Input, Process, Product) evaluation framework. A qualitative approach was employed through interviews, observations, and document analysis involving the principal, vice principal for curriculum, teachers, and education staff. The CIPP model was applied to assess school readiness (context), resource and capacity support (input), the enactment of teaching and supervision (process), and observable outcomes such as teacher practices and student engagement (product). The findings suggest that the principal aligns school vision with curriculum principles (context), supports teacher capacity and learning facilities (input), guides implementation through supervision and collaborative practices (process), and is associated with increased student participation and a more collaborative school climate (product). Learning initiatives, including project-based activities and school-based programs, illustrate how curriculum principles are translated into practice, although variations in teacher readiness and resource use were still observed. Practically, the study suggests that principals may benefit from balancing vision-setting with sustained instructional support, strengthening teacher mentoring, and coordinating resources and partnerships to support implementation. For policymakers, the results may inform leadership development programs that integrate managerial and instructional competencies. This study is limited to a single school context with a small number of participants, so the findings are not intended to be generalized but may offer insight for similar settings.